2005
DOI: 10.1210/jc.2004-1838
|View full text |Cite
|
Sign up to set email alerts
|

Short Stature Caused by a Biologically Inactive Mutant Growth Hormone (GH-C53S)

Abstract: Human GH has two disulfide bridges linking Cys-53 to Cys-165 and Cys-182 to Cys-189. Although absence of the first disulfide bridge has been shown to affect the bioactivity of GH in transgenic mice, little is known of the importance of this bridge in mediating the GH/GH-receptor (GHR) interaction in humans. However, we have identified a missense mutation (G705C) in the GH1 gene of a Serbian patient. This mutation was found in the homozygous state and leads to the absence of the disulfide bridge Cys-53 to Cys-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 29 publications
1
49
0
11
Order By: Relevance
“…To confirm that the mutation P59S does not affect the affinity of the antibody used in DSL-ELISA, two different GH assays were performed on two samples of CHO supernatant and the results were compared (21).…”
Section: Production Of Gh Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm that the mutation P59S does not affect the affinity of the antibody used in DSL-ELISA, two different GH assays were performed on two samples of CHO supernatant and the results were compared (21).…”
Section: Production Of Gh Peptidesmentioning
confidence: 99%
“…Further, six GH variants found in the heterozygous state were suggested to be bioinactive by Millar et al (20), but no clear correlation between laboratory/clinical phenotype and patient genotype was demonstrated. Moreover, in one of the more convincing cases of bioinactive GH reported to date, a homozygous missense mutation C53S in the GH1 gene led to disruption of the disulfide bridge between Cys-53 and Cys-165 in a short Serbian boy (21). Functional studies demonstrated that both GHR binding and Jak2/Stat5 signaling activity were significantly reduced in the GH-C53S compared with wt-GH.…”
Section: Introductionmentioning
confidence: 99%
“…The differential diagnosis of proportional short stature associated with low serum insulin-like growth factor 1 (IGF1) and a normal or high GH peak in a provocation test includes a GH1 mutation leading to a bioinactive GH molecule (1,2) and four well-established causes of GH insensitivity: i) mutations in the GH receptor gene (GHR), affecting the extracellular, transmembrane, or intracellular domains leading to the GH insensitivity syndrome (3,4); ii) mutations of STAT5B, the major component of the GH signaling pathway (3,4,5); iii) IGFALS defects (6); and iv) IGF1 defects (7,8,9,10). In addition, it has been shown that activation of the mitogen-activated protein kinase (MAPK) pathway, as in Noonan syndrome, is associated with partial GH insensitivity (11).…”
Section: Introductionmentioning
confidence: 99%
“…Menos freqüentemente, ocorrem mutações no gene do GH (GH1) com geração de molécula de GH biologicamente inativa (14), ou na STAT5b que provoca defeito pós-receptor de GH (13) (Tabela 5). Defeitos isolados da síntese ou ação do IGF-1 apresentam algumas características laboratoriais semelhantes à IGH, porém apresentam quadro clínico distinto (15-18) (Tabela 5).…”
Section: Investigação Molecular Da Ighunclassified